Detection and quantification of pathogenic Vibrio parahaemolyticus in shellfish by using multiplex PCR and loop-mediated isothermal amplification assay - Tang Yew Huat, John; Tan Turk Hsern, Malcolm; Yoke Kqueen, Cheah (2015)
Vibrio parahaemolyticus is a halophilic bacterium that commonly inhabits the marine and estuarine environments. This organism is also one of the leading causative pathogen of gastroenteritis often related to consumption of raw or undercooked seafood. In this study, molluscan shellfish (bloody clams and surf clams) and crustaceans (shrimps) were monitored in wet markets and hypermarkets. Two molecular methods were employed and compared to detect total and pathogenic V. parahaemolyticus in MPN enrichments: multiplex PCR and LAMP assay. The multiplex PCR was optimized to detect the total (toxR+), tdh+ and trh+ V. parahaemolyticus. On the other hand, the LAMP assay was employed to target the pathogenic strains only, the tdh+ and trh+, respectively. Out of 232 samples examined, 229 (98.7%) were positive for V. parahaemolyticus with counts ranging from 30 to >110, 000 MPN/g. Positive samples for tdh+ V. parahaemolyticus were obtained in 77 out of 232 (33.1%) samples ranging from 30 to >110, 000 MPN/g. Meanwhile, positive samples for trh+ were identified in 16 out of 232 (6.9%) samples examined ranging from 30 to 9600 MPN/g. Detection of samples with presence of tdh+ genes did not vary between methods, but a significant difference was observed when the LAMP assay was compared to PCR to detect trh+ V. parahaemolyticus. Therefore, on occasions where the density of the targeted genes is low, the LAMP assay serves as a better alternative. Nonetheless, this study constitutes an assessment of presence of total and potentially pathogenic V. parahaemolyticus in shellfishes for domestic consumption revealing the potential risk of contracting vibriosis if precautions and safety measures are not properly managed.